2009
DOI: 10.1016/j.neuroscience.2008.12.042
|View full text |Cite
|
Sign up to set email alerts
|

The cerebellum and eye-blink conditioning: learning versus network performance hypotheses

Abstract: Classical conditioning of the eyeblink reflex is a form of motor learning that is uniquely dependent on the cerebellum. The cerebellar learning hypothesis proposes that plasticity subserving eyeblink conditioning occurs in the cerebellum. The major evidence for this hypothesis originated from studies based on the telecommunications network metaphor of eyeblink circuits. These experiments inactivated parts of cerebellum-related networks during the acquisition and expression of classically conditioned eyeblinks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 50 publications
(61 reference statements)
4
41
0
Order By: Relevance
“…Also, the contribution of the cerebellar cortex could play an important function on the actual phase-modulating mechanism of IP neurons during performance of learned movements. Purkinje cells, acting via their collateral and interneuronal networks in addition with the participation of the olivary system (Velarde et al, 2004;Bracha et al, 2009), may contribute for maintaining the information dynamics during and between trials (Hong and Optican, 2008). The recent demonstration of the existence of the "brain states" (Poulet and Petersen, 2008) determined by oscillation of the membrane potential in synchronized pyramidal cells may be compared with our experimental data showing similar oscillation in the OO MNs (Trigo et al, 1999;SĂĄnchez-Campusano et al, 2007).…”
Section: Discussionmentioning
confidence: 59%
“…Also, the contribution of the cerebellar cortex could play an important function on the actual phase-modulating mechanism of IP neurons during performance of learned movements. Purkinje cells, acting via their collateral and interneuronal networks in addition with the participation of the olivary system (Velarde et al, 2004;Bracha et al, 2009), may contribute for maintaining the information dynamics during and between trials (Hong and Optican, 2008). The recent demonstration of the existence of the "brain states" (Poulet and Petersen, 2008) determined by oscillation of the membrane potential in synchronized pyramidal cells may be compared with our experimental data showing similar oscillation in the OO MNs (Trigo et al, 1999;SĂĄnchez-Campusano et al, 2007).…”
Section: Discussionmentioning
confidence: 59%
“…In clear opposition to the proposal that the RN is a mere relay premotor center conveying motor commands emanating from the cerebellum-the latter being the proper neuronal site where the acquisition and storage of newly acquired eyelid conditioned responses take place (Chapman et al, 1990;Bracha et al, 1993Bracha et al, , 2009Krupa et al, 1993;Freeman and Steinmetz, 2011)-the RN was one of the first places where activity-dependent changes in synaptic strength was supposed to occur (Tsukahara, 1981). In a series of seminal experiments, Tsukahara et al (1981) and Murakami et al (1987Murakami et al ( , 1988, as well as additional groups (Ito and Oda, 1994;Pananceau et al, 1996), suggested that RN magnocellular neurons could be capable of synaptic plastic changes during the acquisition of different types of skeletal associative learning tasks.…”
Section: Learning-dependent Changes In the Neuronal Activity Of Rn Anmentioning
confidence: 85%
“…In a seminal study, Chapman et al (1990) performed multiunitary recordings of putative RN neurons and the reversible lidocaine inactivation of both red and IP nuclei during classical conditioning of behaving rabbits, concluding that the RN acts as a relay nucleus for motor commands generated at cerebellar circuits. In this regard, it has been reported that RN inactivation produced no effect on the acquisition process (Grant and HorcholleBossavit, 1986;Clark and Lavond, 1993;Krupa et al, 1993;Robleto and Thompson, 2008), a point of view still accepted by many groups (Bracha et al, 2009;Freeman and Steinmetz, 2011). In dissension, early (Kennedy and Humphrey, 1987;Schmied et al, 1988;Cartford et al, 1997) and recent studies (Miller and Gibson, 2009) proposed that the RN plays a more active role in motor learning processes.…”
Section: Different Roles Ascribed To Red Nucleus Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, acquisition curves depend on the selected criterion and, as indicated earlier, Lurcher mice present eyelid responses smaller than those of their corresponding controls (see Porras-GarcĂ­a et al 2005). Thus and for the appropriate choice of a comparable criterion, it is always necessary to check the effects of cerebellar lesions not only on reflex blink responses, but also on the kinematics of conditioned responses-that is, differences between learning and performance should always be taken into account (Bracha et al 2009;Delgado-GarcĂ­a and Gruart 2006;JimĂ©nez-DĂ­az et al 2004;Van Alphen et al 2002;Wells and Harvey 1989). Interestingly, following the electrolytic lesion of the interpositus nucleus, the learning curves of both wild-type and Lurcher mice were severely affected.…”
Section: Contribution Of Cerebellar Structures To the Generation Of Ementioning
confidence: 99%